Au-catalyzed ultrathin copper nanowires. Issue 48 (1st December 2022) - Xu, Juan; Zhu, Xingzhong; Xia, Sihao; Liu, Yang; Kan, Caixia; Shi, Daning
Abstract : Ultrathin Cu nanowires with diameters as thin as 7 nm are synthesized through introducing Au nanoparticles as catalytic sites and diameter controllers. Abstract : Decreasing the diameter of copper nanowires has been proven to be an effective method to improve their optoelectronic performance by lessening light attenuation. There is as yet no published literature for producing copper nanowires with diameters below 10 nm. Herein, we report a general aqueous approach to the synthesis of ultrathin copper nanowires with average diameters as thin as 7 nm and aspect ratios of up to 1400 for the first time. The key to the success of this synthesis is the introduction of the five-fold twinned Au nanoparticles. The systematic investigation of the growth process reveals that the copper nanowires evolve from one side of the Au nanoparticles and adopt a penta-twinned structure because of the lattice mismatch between Cu and Au (11.4%), which is verified by first-principles calculations. The diameter and length of copper nanowires possess excellent tunability as the size of the Au nanoparticles varied. The fabricated transparent conductive films based on ultrathin copper nanowires exhibit excellent flexibility and optoelectronic properties.